The Contribution of Profit-sharing Characteristics to the Performance of Islamic Banks - Hanafi, Syafiq Mahmadah (IAIN Surakarta, 2021)
Islamic commercial banks are highly identic with the profit-sharing as a sharia banking basic operational system. The profit-sharing becomes a specific characteristic of sharia banks as well as a distinction from conventional banks. Hence, this study aims to examine if the profit-sharing characteristic contributes to the performances of Islamic commercial banks in Indonesia. This study employed time series data derived from the Financial Service Authority (OJK) using regression-mixed test and auto-regressive heteroscedasticity (ARCH). The results pointed out that the profit-sharing system for the lending of Musharaka had an impact on the performance of sharia banks; while the profit-sharing for the funding of Mudaraba did not support the hypothesis with negative coefficient. The results suggest that the profit-sharing characteristic provides contribution to the performance of Islamic commercial banks through the lending of Musharaka. These results further indicate that the profit-sharing characteristic performed by Islamic commercial banks is proven to be effective in improving their performances. This study’s results have an implication for Islamic commercial banks to strengthen their profit-sharing characteristics and improve the public trust toward sharia banking system.